Efektifitas Media Edukasi berbasis Augmented Reality terhadap Peningkatan Pengetahuan Pola Makan Sehat dalam Pencegahan Diabetes Mellitus - Tajaruddin, Muhammad; Wahana, Hijratun; Kusuma Negara, Candra; Prawira, Ricky (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
The increasing cases of Type 2 Diabetes Mellitus (T2DM) in adolescents is a serious challenge in public health. Unhealthy eating patterns and low nutritional literacy are the main risk factors. This study aims to analyze the effectiveness of augmented reality (AR)-based e-booklet educational media in improving students' quality of life (QoL) through healthy eating education. The study used a quasi-experimental design of the one-group pretest-posttest type on 115 grade XI students at a high school in Banjarmasin in May – June 2025. The research instrument was a QoL questionnaire consisting of five aspects: satisfaction with therapy, the effect of therapy on life, fear of complications, social problems, and total QoL score. Data analysis used a paired sample t-test with the Kolmogorov–Smirnov normality test. The results showed a significant increase in all aspects of QoL, with a p value <0.001 for all variables. The total QoL score increased from 11.38 ± 1.86 to 14.52 ± 1.39 after the intervention. These findings indicate that AR e-booklet media is effective in improving students' understanding and has a positive impact on emotional, social, and attitudinal aspects of health. In conclusion, AR-based education is an innovative approach that not only improves knowledge but also the quality of life of adolescents in the context of DM Type II prevention.